Curriculum and professional training/mathematics education - Silva, Euclides Ferreira da; Ferreira, Ângela Nascimento; Sá, Jeruzalem Martins de; Gonsalves, Gabriel Lima; Silva , Surama da Conceição; Silva, Maria Altair Ferreira da; Lima, Davi Oliveira (Seven Editora, 2023)
This article discusses curriculum and teacher education, it originated from documental analysis in which we discuss several readings of authors who discuss the topic in question.In this sense, the inadequate training of teachers is described, in which their formative learning is theory and what happens in practice is different from academic teaching. Therefore, we concluded that it is quite complex to make Curriculum changes in a specific subject without considering changes in the general curriculum of educational institutions. DOI:https://doi.org/10.56238/alookdevelopv1-083